2021
DOI: 10.3390/biom11091353
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Secretome Analysis Suggests Differential Pathogenic Mechanisms between Fusarium oxysporum f. sp. cubense Race 1 and Race 4

Abstract: Banana Fusarium wilt, caused by the fungus pathogen Fusarium oxysporum f. sp. cubense (Foc), is a devastating disease that causes tremendous reductions in banana yield worldwide. Secreted proteins can act as pathogenicity factors and play important roles in the Foc–banana interactions. In this study, a shotgun-based proteomic approach was employed to characterize and compare the secretomes of Foc1 and Foc4 upon banana extract treatment, which detected 1183 Foc1 and 2450 Foc4 proteins. Comprehensive in silico a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Plant pathogens employ effectors as molecular weapons to manipulate host immunity and facilitate colonization ( Bi and Zhou, 2021 ). Recent studies have shown that the effector proteins secreted by Foc4 can act as pathogenicity factors and play important roles in Foc-banana interaction ( Li et al, 2019 ; He et al, 2021 ). Almost 1,000 putative secreted proteins have been predicted in Foc genome, many of which are thought to be candidates for effector proteins ( Guo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Plant pathogens employ effectors as molecular weapons to manipulate host immunity and facilitate colonization ( Bi and Zhou, 2021 ). Recent studies have shown that the effector proteins secreted by Foc4 can act as pathogenicity factors and play important roles in Foc-banana interaction ( Li et al, 2019 ; He et al, 2021 ). Almost 1,000 putative secreted proteins have been predicted in Foc genome, many of which are thought to be candidates for effector proteins ( Guo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type strain and the transformants generated in this study were grown at 28°C on PDA medium for 5 days to assess growth and colony characteristics. Czapek Dox (CD) medium was used for conidiation assays and liquid NCMB medium was used to mimic the Foc-banana interaction as described ( He et al, 2021 ). The Foc TR4-susceptible banana cultivar Brazilian (AAA group, Cavendish) and tobacco ( Nicotiana benthamiana ) were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations